A Simplified Approach for Ocular Rehabilitation - A Case Report - Manandhar, P; Mathema, S R.B. (Journal of Nepalese Prosthodontic Society, 2020)
Loss of an eye or any body part has an intimidating and crippling effect on the psychosocial well-being of the patient. Although the artificial prosthesis cannot restore the function, it can highly improve the patient’s esthetics and help them regain their psychological confidence. Literature has advocated various rehabilitation modalities including empirical use of stock shells, modifying stock eyes, custom-made ocular prostheses, ocular implants, etc. A custom-made ocular prosthesis, among all the techniques, shows improved adaptation to tissue bed, distributes uniform pressure, provides a more esthetic and precise result, and is relatively cost-effective. This case report explores a relatively comprehensive method of custom ocular prosthesis fabrication for an ocular defect with a satisfactory outcome.